2021
DOI: 10.1126/scitranslmed.aaz6804
|View full text |Cite
|
Sign up to set email alerts
|

A selective HDAC8 inhibitor potentiates antitumor immunity and efficacy of immune checkpoint blockade in hepatocellular carcinoma

Abstract: Insufficient T cell infiltration into noninflamed tumors, such as hepatocellular carcinoma (HCC), restricts the effectiveness of immune-checkpoint blockade (ICB) for a subset of patients. Epigenetic therapy provides further opportunities to rewire cancer-associated transcriptional programs, but whether and how selective epigenetic inhibition counteracts the immune-excluded phenotype remain incompletely defined. Here, we showed that pharmacological inhibition of histone deacetylase 8 (HDAC8), a histone H3 lysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 71 publications
1
81
1
Order By: Relevance
“…These observations implied that the infiltration of these immune cell subtypes might exert an important influence on the prognosis of HCC patients. Given the clinical importance of therapeutic strategies based on immune checkpoint blockade in HCC (32,33), we then explore the association between the risk score and several immune checkpoints, such as PD1, PDL1, CTLA4, VSIR, and B7H3. As shown in Figure 7F, the heat map showed the positive relations between risk score and these immune checkpoints.…”
Section: Gsea Enrichment and Immunity Analysis Of The Risk Scorementioning
confidence: 99%
“…These observations implied that the infiltration of these immune cell subtypes might exert an important influence on the prognosis of HCC patients. Given the clinical importance of therapeutic strategies based on immune checkpoint blockade in HCC (32,33), we then explore the association between the risk score and several immune checkpoints, such as PD1, PDL1, CTLA4, VSIR, and B7H3. As shown in Figure 7F, the heat map showed the positive relations between risk score and these immune checkpoints.…”
Section: Gsea Enrichment and Immunity Analysis Of The Risk Scorementioning
confidence: 99%
“…For instance, HDACi in combination with anti-PD-1 or anti-CTLA-4 antibodies were found to promote the production of granase B in activated CD8 + T responder cells, significantly improving the infiltration and function of innate immune cells and enhancing adaptive immune response. Using a hepatocellular carcinoma preclinical model, selective HDAC8 inhibition was found to exert effective responses to anti-PD-L1 treatment by reactivating the production of T cell-trafficking chemokines ( 107 ). CG-745, a member of HDACi, has been validated to modulate the immune microenvironment and enhance the therapeutic effect of anti-PD-1 ICIs, which indicates the effectiveness of the combined application of HDACi and ICIs ( 108 ).…”
Section: Combined Application Of Hdaci and Icismentioning
confidence: 99%
“…et al, 2018 ). However, opposite studies have shown that HDAC8 inhibition increases the expression of NKG2D ligand in glioma cells which enhanced the recognition ability and cytotoxicity of NK cells, and activates immune cells in hepatocellular carcinoma resulting in an effective and lasting response to ICB ( Yang W. et al, 2021 ; Mormino et al, 2021 ). On the contrary, HDAC9 and HDAC10 are opposite to HDAC8 in up-regulating PD-L1.…”
Section: Histone Deacetylases In Tumor Immunity Regulationmentioning
confidence: 99%